Simple synthesis of heterocyclic benzo[f]azulene isosters. Construction of a 2-benzazepine fragment in the Pictet—Spengler reaction - Bogdan, N.M.; Ivanysenko, O.V.; Sujkov, S.Yu.; Yakovleva, H.V.; Shved, O.M.; Bogza, S.L. (Reports of the National Academy of Sciences of Ukraine, 2022)
The synthesis of 5-amino-4-benzylpyrazoles and their reactions with carbonyl compounds under the Pictet— Spengler reaction conditions were studied. A simple preparative method for the synthesis of 4-(3, 4-dimethoxybenzyl)- 3(5)-aminopyrazoles, reactive polyfunctional compounds has been developed. A new method of formation of a 2-benzazepine fragment under the Pictet—Spengler conditions on the example of a new heterocyclic system of 5, 10-dihydro-4H-pyrazolo[3, 4-c][2]benzazepine has been developed. Based on NMR studies, it was found that the spatial structure of the azepine cycle in the obtained heterocycles depends on the size and nature of the carbonyl reagent radical. The found compounds with activity against the leishmaniasis pathogen, which exceeds the known ones.